FROM ERNEST HEMINGWAY TO HARUKI MURAKAMI: PRESENCE AND ABSENCE DICHOTOMY, IDENTITY CRISIS AND THE SEARCH FOR MEANING THAT WOMEN CHARACTERS BRING ABOUT IN “IN ANOTHER COUNTRY” AND “KINO” - Zafer Şafak (Toplum ve Kültür Araştırmaları Dergisi)
The stories “In Another Country” in Men Without Women (1927) and “Kino” in Men Without Women (2014) are two different but profoundly related short stories written by Ernest Hemingway and Haruki Murakami respectively. Although these two short stories differ by virtue of spatial and temporal variables producing the cultural climate in which the two novelists lived and created their works, by reading these two short stories closely and comparatively, this study aims to point out, prove and comment that both stories reveal the same themes in their narratives as the problematization of men’s relationship with the women together with the impacts of the presence-absence of women figures on men’s lives. The men in “In Another Country” and “Kino”, whose identity crises and search for meaning together with their conditions are analyzed critically, are either proved to be ostensibly indifferent and have some sort of purported stamina or they are implicitly fragile and emotionally imbalanced due to the sorrows they go through and are not able to overcome. Examination of the stories unearths the psychologies of the male characters who have either misunderstood women or misinterpreted their existential conditions. By examining the two short stories critically and comparatively, this study aims to demonstrate while both stories indeed closely revolve around such notions of identity, love, life, unhappiness, isolation and search for meaning in the middle of literal and metaphorical crises due to the presence and absence of one’s beloved, it provides a chance of scrutinizing the intricate dynamics of male and female relationships as well. Focusing on the way through which the dichotomy of presence and absence of female protagonists directs the male protagonists’ course of lives and how it leads them to identity crises and the search for meaning, a comparative analysis and close reading of the two short stories in question are thought to provide rich and evocative results.